Aplikasi Pengenal Jenis Kulit Wajah Skintest With Your Dream Face Beauty - Sofyan Mufti Prasetiyo; Astalia Putri Yuniasih; Raudhatul Zannah; Umirah (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Beauty is often identified with smooth white facial skin. However, facial skin cannot be bleached carelessly with ingredients and must also be adjusted to the type of skin. According to beauty experts, there are five types of skin with their respective characteristics and characteristics. Where there are normal, dry, oily, combination and sensitive skin. In order to choose skincare that is safe and according to facial skin type, we will build a YDF Beauty skintest application. YDF (Your Dream Face) Beauty is a free skin care application on mobile phones. Research This study uses the waterfall development method and qualitative descriptive research methods. Application development with the waterfall method goes through several stages such as the stages of needs analysis, system design, coding, testing and development. During the testing phase, everything went according to plan. The results of making the Skintest with YDF Beauty application can run according to its function and run well. This application is expected to help consumers get to know their facial skin type, find out skin problems and easily choose skincare with good quality local products and at economical prices.